Chemotherapeutics in the treatment of multiple sclerosis - Bernd C. Kieseier (Therapeutic Advances in Neurological Disorders, 2010)
The likely pathogenic mechanisms of multiple sclerosis (MS) provide a sound rationale for investigating the efficacy of drugs possessing immunosuppressive or immunomodulatory properties. With proven efficacy, safety and tolerability, interferon beta formulations and glatiramer acetate have become the mainstay of initial treatment for patients with relapsing forms of MS. More recently, natalizumab, a humanized monoclonal antibody (mAb) against the cellular adhesion molecule α4-integrin, has been employed for patients with an inadequate response or lack of tolerability to an alternate MS therapy, or as initial therapy for patients with severe disease. Various agents initially developed for oncological indications, either as chemotherapeutics or mAbs, may also have current or future uses in MS treatment. Mitoxantrone is currently the only chemotherapeutic agent approved for treatment of MS in the United States, while in parts of Europe azathioprine is approved and widely used for MS treatment. Other chemotherapeutics that have been tested in MS to date include cyclophosphamide, methotrexate, cladribine, and the mAbs alemtuzumab and rituximab. While there has been varying evidence of efficacy for these compounds, each appears to be associated with serious risks that require careful consideration and management. Given the risks that have been demonstrated for available chemotherapeutic agents and while long-term postmarketing safety data are still not available for those agents in development, it seems prudent to carefully assess the possible use of chemotherapeutics in the treatment of MS. A thorough risk-benefit analysis is becoming increasingly important in the assessment of therapeutic options for this disabling disease.